Educación y conducta sexual de los y las adolescentes de octavo, noveno, y décimo año de educación básica de la Unidad Educativa Santísimos Corazones de la ciudad de Pasaje, provincia de El Oro, periodo lectivo 2011-2012. - Correa Marín, Sandra Mónica (2012)
In the consumer society in which we live it is not surprising that sex is also marketed, misrepresenting how wonderful it should be an intimate relationship between man and woman as complementary beings. Sex - trade creates stereotypes in both boys and girls when the physical aspect of sexual partner, creates myths about relationships, increasingly dehumanizing where the acting beings only seeking personal satisfaction, mastery of the couple . When the opposite of all this is needed today humanizes dora sex education.